QDB: a new database of plasma chemistries and reactions. (4th April 2017) - Tennyson, Jonathan; Rahimi, Sara; Hill, Christian; Tse, Lisa; Vibhakar, Anuradha; Akello-Egwel, Dolica; Brown, Daniel B; Dzarasova, Anna; Hamilton, James R; Jaksch, Dagmar; Mohr, Sebastian; Wren-Little, Keir; et al.
Abstract: One of the most challenging and recurring problems when modeling plasmas is the lack of data on the key atomic and molecular reactions that drive plasma processes. Even when there are data for some reactions, complete and validated datasets of chemistries are rarely available. This hinders research on plasma processes and curbs development of industrial applications. The QDB project aims to address this problem by providing a platform for provision, exchange, and validation of chemistry datasets. A new data model developed for QDB is presented. QDB collates published data on both electron scattering and heavy-particle reactions. These data are formed into reaction sets, which are then validated against experimental data where possible. This process produces both complete chemistry sets and identifies key reactions that are currently unreported in the literature. Gaps in the datasets can be filled using established theoretical methods. Initial validated chemistry sets for SF6 /CF4 /O2 and SF6 /CF4 /N2 /H2 are presented as examples.